Voices of black graduate deans in advancing graduate education at historically white universities - Frierson, Henry T. 1944- (Diversity in higher education ;, 2025)
Black graduate deans at historically white institutions have long navigated the complexities of higher education leadership while advocating for diversity, equity, and student success. This compelling volume brings together their stories, insights, and strategies for transforming graduate education. From breaking barriers to fostering inclusive faculty cultures, these leaders share how their lived experiences and collective knowledge have shaped programs that empower all students. Through personal narratives and institutional case studies, this edited collection highlights the resilience, innovation, and impact of Black graduate deans, offering essential guidance for educators, administrators, and policymakers committed to meaningful change.